Benefit duration, job search behavior and re-employment - Andreas Lichter; Amelie Schiprowski (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
This paper studies how the potential duration of unemployment benefits affects early job search behavior and re-employment outcomes. We exploit an unexpected reform of the German unemployment insurance (UI) scheme in 2008, which increased the potential benefit duration from 12 to 15 months for benefit recipients of age 50 to 54. Based on detailed survey data and a difference-in-differences design, we estimate that one additional month of potential benefits reduces early job applications by around 10%. Using social security data, we further find that the extension of benefits increases the average nonemployment duration of individuals entering UI after the reform. Among individuals who got treated at later stages of their unemployment spell, the increased UI coverage does not appear to come at the cost of longer nonemployment. A cautious back-of-the-envelope calculation reveals substantial job funding returns to early search effort.
Keywords: D83; I38; J64; J68; 330; Unemployment Insurance; Job Search; Re-Employment Outcomes; Natural Experiment